The Effect Of Using Question-Answer Relationship (QAR) On Students’ Reading Comprehension Abilities In Procedure Text - Wijayanto, Rori; Firharmawan, Hastri (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
This research aims to discover how well the students' reading comprehension abilities are enhanced by QAR strategy and to discover how the students’ responses to the use of QAR strategy. The population in this research were students of 10th grade SMK Ma’arif 9 Kebumen which consisted of 507 students and the sample consisted of 60 students. This research used a quantitative and data was gathered from the test result as well as a questionnaire containing 16 questions with an item scale. The test result in experimental class showed that the pre-test average was 55.6 while the post-test was 82.2. The average score of both is quite different. After hypothesis testing was carried out, the results obtained were T Score < T Table (0,000<0,05), Therefore, it can be said that using QAR has an impact on students' reading comprehension abilities of 10th grade students in SMK Ma’arif 9 Kebumen. In addition, the students also showed positive responses to the use of QAR strategy such as the students were able to mark keywords from the text to find the correct answer, the students were able to explain the information contained in the reading text, and the students said that the QAR strategy facilitated them to understand the reading text and to answer the questions. It was evident from the results of the questionnaires. Most of students stated that the QAR technique was highly beneficial and helped them enhance their reading comprehension skills.